2020
DOI: 10.1002/acn3.51115
|View full text |Cite
|
Sign up to set email alerts
|

Baseline neuropsychological profiles in prion disease predict survival time

Abstract: Objective: Few studies have captured the neuropsychological profile of sporadic Creutzfeldt-Jakob disease (sCJD) with neuropsychological testing, and little is known about cognitive predictors of survival. We characterized baseline neuropsychological performance in sCJD and investigated associations with survival. Methods: sCJD participants who completed the MMSE (n = 118), 61 sCJD of whom also completed a neuropsychological battery at baseline, and 135 age-matched healthy controls, were included. Composite sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Staffaroni et al . 16 identified CSF biomarkers associated with survival and Sundaram et al 17 used a neuropsychological assessment score to predict probability of 3-, 6- and 12-month survival though neither tested combinations of predictors. Llorens et al .…”
Section: Introductionmentioning
confidence: 99%
“…Staffaroni et al . 16 identified CSF biomarkers associated with survival and Sundaram et al 17 used a neuropsychological assessment score to predict probability of 3-, 6- and 12-month survival though neither tested combinations of predictors. Llorens et al .…”
Section: Introductionmentioning
confidence: 99%
“…Staffaroni et al identified cerebrospinal fluid (CSF) biomarkers associated with survival 16 and Sundaram et al used a neuropsychological assessment score to predict probability of three-, six-and twelve-month survival 17 though neither tested combinations of predictors. Llorens et al developed a prognostic model of 6-month survival from sCJD symptom onset incorporating age, sex, PRNP codon 129 genotype, and CSF tau, which whilst valuable, did not model survival from the point of clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…identified cerebrospinal fluid (CSF) biomarkers associated with survival 16 and Sundaram et al . used a neuropsychological assessment score to predict probability of three-, six- and twelve-month survival 17 though neither tested combinations of predictors. Llorens et al .…”
Section: Introductionmentioning
confidence: 99%